2014
DOI: 10.1371/journal.pone.0098171
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL Enhances Apoptosis of Human Hepatocellular Carcinoma Cells Sensitized by Hepatitis C Virus Infection: Therapeutic Implications

Abstract: Hepatitis C virus (HCV) infection causes chronic liver diseases leading to hepatocellular carcinoma (HCC) and liver failure. We have previously shown that HCV sensitizes hepatocytes to mitochondrial apoptosis via the TRAIL death receptors DR4 and DR5. Although TRAIL and its receptors are selective targets for cancer therapy, their potential against HCC with chronic HCV infection has not been explored yet. Here we show that HCV induces DR4/DR5-dependent activation of caspase-8 leading to elevation of apoptotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Virus-induced sensitization of infected target cells in response to TRAIL-induced apoptosis has been reported in various viruses, including respiratory syncytial virus, hepatitis B virus, hepatitis C virus, HIV, SIV, and Hendra virus (61)(62)(63)(64)(65)(66)(67)(68). Notably, in agreement with the present study (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Virus-induced sensitization of infected target cells in response to TRAIL-induced apoptosis has been reported in various viruses, including respiratory syncytial virus, hepatitis B virus, hepatitis C virus, HIV, SIV, and Hendra virus (61)(62)(63)(64)(65)(66)(67)(68). Notably, in agreement with the present study (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In general, a modest upregulation of TRAIL is reported during acute infection (Werner et al, 2013 ; Golden-Mason et al, 2014 ) and it appears to remain elevated during chronic infection. TRAIL receptors are also upregulated on HCV infected hepatocytes (Jang et al, 2014 ). Increased TRAIL expression on NK cells has also been associated with an ability to induce apoptosis of hepatitis stellate cells and potentially inhibit HCV associated development of fibrosis (Glässner et al, 2012 ).…”
Section: Nk Cells Have Altered Phenotype and Function In Chronic Hcv mentioning
confidence: 99%
“…Interestingly, DR5 upregulation was found in the PEI/DNA high NPs ( Figure 12F ). It was reported that virus transfection can stimulate the upregulation of DR5 expression 27. It was thus suspected that the PEI-mediated transfection could have a similar effect on DR5 upregulation.…”
Section: Resultsmentioning
confidence: 99%